Inhibition of microlax- Induced experimental diarrhoea with narcotic like-extracts of psidium guajava leaf in rats - Lutterodt, George D. (1999)
Measurement of rates of propulsion in the small intestine in control and experimental groups of male Sprague-Dawley rats (200-250 g) were carried out as a means of assessing antidiarrhoeal activity of aqueous extracts of the leaf of Psidium guajava (Linn.), using morphine as the standard drug of reference. Hyperpropulsion (diarrhoea) was induced by gavaging rats in_a control group with Microlax, using phenol red mixed into it as a marker in the intestine and the mean rate of the hyperpropulsion was determined. The normal rate of propulsioh, defined as the percentage of the length of the ileum traversed by the front of the dye in 1 h after gavaging animals·with a liquid paraffin-phenol red meal, was also determined in another control group.